2006
DOI: 10.1097/00000542-200605000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Regional Differences in Rocuronium Bromide Dose–Response Relation and Time Course of Action

Abstract: The authors demonstrated a significant difference in rocuronium potency and duration of action among patients in the three countries. Larger studies are required for determining dosage recommendations for different geographic regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 11 publications
1
26
1
Order By: Relevance
“…1 Our group also demonstrated a geographic difference concerning a neuromuscular blocking agent, as the duration of action of rocuronium was significantly longer in Han Chinese patients in China than in Caucasians in Austria. 15 On the other hand, our study results do not concur with other individual studies that failed to reveal or precisely quantify differences between Caucasian and Chinese populations. 7,8 Two separate studies conducted by the same team implementing the same study design reported almost 8 However, this could also indicate that a pharmacokinetic explanation seems to be a more plausible explanation rather than a pharmacodynamic one.…”
Section: Discussioncontrasting
confidence: 99%
“…1 Our group also demonstrated a geographic difference concerning a neuromuscular blocking agent, as the duration of action of rocuronium was significantly longer in Han Chinese patients in China than in Caucasians in Austria. 15 On the other hand, our study results do not concur with other individual studies that failed to reveal or precisely quantify differences between Caucasian and Chinese populations. 7,8 Two separate studies conducted by the same team implementing the same study design reported almost 8 However, this could also indicate that a pharmacokinetic explanation seems to be a more plausible explanation rather than a pharmacodynamic one.…”
Section: Discussioncontrasting
confidence: 99%
“…Clinically, anesthesiologists in Korea and Japan have sometimes experienced unacceptable intubation conditions after administration of a standard dose of rocuronium. It is unknown whether the ethnicity of the patient can directly affect rocuronium potency but Dahaba et al [2] have reported geographic regional differences in the rocuronium dose–response relation and time course of action. They have shown that the ED 95 of rocuronium is significantly higher in Chinese patients than in American patients (475 ± 155 μg/kg vs 362 ± 149 μg/kg, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that, in obese patients, the duration of action of rocuronium was significantly prolonged when the drug was infused according to total body weight (TBW) [8,9]. Moreover, geographical differences in rocuronium potency and duration of action have also been found [10].…”
Section: Introductionmentioning
confidence: 99%